Online Identity Management and Relational Closeness: The Mediating Role of Emotional Transparency - Abdulhussein, Omar; El Amrani, Youssef; El-Sayed, Mona (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the direct and indirect effects of online identity management on relational closeness among social media users, with emotional transparency modeled as a mediating variable.Methods and Materials: A descriptive correlational research design was employed with 400 adult social media users in Egypt, selected according to the Morgan and Krejcie sample size table. Participants completed validated self-report scales assessing online identity management, emotional transparency, and relational closeness. Data analysis was conducted using SPSS-28 for descriptive and correlational statistics and AMOS-21 for structural equation modeling (SEM). Model fit was evaluated with χ², χ²/df, GFI, AGFI, CFI, TLI, and RMSEA.Findings: Online identity management correlated positively with both emotional transparency (r = .42, p < .001) and relational closeness (r = .37, p < .001). Emotional transparency was strongly associated with relational closeness (r = .56, p < .001). The SEM analysis showed an excellent model fit, χ²(73) = 143.62, χ²/df = 1.97, GFI = .93, AGFI = .90, CFI = .96, TLI = .95, RMSEA = .049. Online identity management significantly predicted emotional transparency (β = .42, p < .001) and relational closeness directly (β = .22, p = .002). Emotional transparency strongly predicted relational closeness (β = .51, p < .001) and mediated the relationship between online identity management and closeness (indirect β = .21, p < .001). The total effect of online identity management on relational closeness was moderate to strong (β = .43, p < .001).Conclusion: Findings demonstrate that while strategic online identity management helps build closeness, its impact is significantly strengthened by emotional transparency. By openly sharing genuine emotions, individuals transform managed digital personas into meaningful and intimate connections.